2017
DOI: 10.1155/2017/5135429
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Studies and Translational Applications of Intracerebral Hemorrhage

Abstract: Intracerebral hemorrhage (ICH) which refers to bleeding in the brain is a very deleterious condition with high mortality and disability rate. Surgery or conservative therapy remains the treatment option. Various studies have divided the disease process of ICH into primary and secondary injury, for which knowledge into these processes has yielded many preclinical and clinical treatment options. The aim of this review is to highlight some of the new experimental drugs as well as other treatment options like stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 192 publications
(193 reference statements)
0
7
0
Order By: Relevance
“…ICH is a type of stroke characterized by spontaneous and nontraumatic bleeding in the brain that is associated with high morbidity and mortality rates [ 1 ]. ICH can be classified as primary and secondary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICH is a type of stroke characterized by spontaneous and nontraumatic bleeding in the brain that is associated with high morbidity and mortality rates [ 1 ]. ICH can be classified as primary and secondary.…”
Section: Introductionmentioning
confidence: 99%
“…ICH can be classified as primary and secondary. While treatment options for the former are limited, various strategies have been proposed for managing the latter [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is no effective treatment for ICH. While recombinant factor VIIa (rFVIIa) therapy ( 71 74 ), minimally invasive intracranial hematoma removal ( 75 ), immunosuppressant therapy (e.g., fingolimod) ( 74 , 76 79 ), nanomedicine ( 80 , 81 ), stem cell transplantation ( 82 86 ), and treatment with anti-neuroinflammatory, anti-oxidative, and neuroprotective agents ( 87 89 ) may produce some therapeutic effects, such treatments have failed to achieve breakthrough results. Some researchers have speculated that there may be a “time window” for effective treatment for ICH, similar to that observed for ischemic stroke.…”
Section: Ho-1 and Ichmentioning
confidence: 99%
“…Microglia, which are often referred to as phagocytes in the brain, are the primary immune effector cells of the CNS. Microglia can exert both neurotoxic and restorative effects, depending on the type of stimulation, intensity and duration of the stimulus, microenvironment, interactions with other cells, and patient age ( 87 ). Zhang et al ( 14 ) revealed that HO-1 is abundantly expressed in microglia in the early stages after ICH, increasing microglial activation and aggravating neurological impairments.…”
Section: Ho-1 and Ichmentioning
confidence: 99%
“…ICH is a serious medical emergency that occurs when blood vessels rupture within the brain. Till date, there are three main techniques that are widely used in the study of ICH: autologous blood injection, collagenase blood injection, and microballoon injection (Siaw‐Debrah et al, ). However, there is no effective surgical or medical treatment that is available to improve the functional outcomes in patients with ICH, which is because the underlying mechanisms are complex (Fiorella, Zuckerman, Khan, Ganesh Kumar, & Mocco, ).…”
Section: Introductionmentioning
confidence: 99%